“Everybody has their own Dream”: Nail houses and Resistance to the Landscape of Globalization in Contemporary China - Szwedska, Thomas (eTopia, 2017)
The transformation of the Chinese landscape is embodied by the figure of new, hyper-modern cityscapes. With the influx of hundreds of millions of people from rural to urban areas, China’s economic reform process is dominated by the production of space designed to instill a new ideal of modern economic subjects for Chinese identity. However, China’s modernization is complicated by the emergence of a recent urban phenomena: dingzihu, or nail-houses. Nail- houses are points of resistance where individuals refuse to abandon their homes when traditional urban districts are demolished for urban renewal. By examining personal testimonies of nail-house inhabitants and visual representations of traditional urban communities in contemporary Chinese cinema, it will be argued that nail-house protests’ resistance to the disappearance of traditional urban-community culture is a symptom of the logic of globalization. To this end, Frederic Jameson shall be invoked to argue that globalization forces the creation of local national worlds that are antagonistic to all others, including those within their own space. Drawing on Hannah Arendt, insofar as the collapse of the public and private sphere for the sake of economic interest in China can be understood as reducing the difference of personal identity to create national homogeneity, nail-house protests reveal a common condition of exile endemic to the process of global modernity as a whole.